Control of a 3 level PWM inverter for grid-connected photovoltaic generation systems - Zhao, Yuanshi (Nanyang Technological University, 2022)
This thesis introduces different topologies of three-level inverter and compares the working principle of them, analyzes the advantage of T-type inverter and introduce the SPWM and SVPWM. Two modeling method: carrier disposition and SVPWM are introduced and the calculation of the two modulations are compared. In the modeling part, the PSIM simulation model of the carrier disposition and SVPWM are applied and the result of the two control models have been analyzed.